Application of Cyclosporine A Plus Zishen Yutai Pill in the Treatment of Patients with Recurrent Pregnancy Loss - Mingzhe Zhang; Min Xu; Li Li; Min Dong; Haiyan Wang; Keyan Luo (Journal of Investigative Surgery)
Objective This study analyzed the therapeutic effects of cyclosporine A (CsA) plus Zishen Yutai Pill (ZYP) in the treatment of patients with recurrent pregnancy loss (RPL).Methods This study prospectively included 150 RPL patients who were randomized into CsA and CsA + ZYP groups (n = 75 patients/group). The serum levels of hormones estradiol (E2), human chorionic gonadotropin (HCG), progesterone (P), Th1-type cytokines, and Th2-type cytokines were detected by ELISA. Additionally, we compared the proportions of immune cell subsets (T lymphocytes, Th1, Th2), the incidence of adverse reactions, and live birth rates between the two groups. Furthermore, patients treated with CsA plus ZYP were categorized into appropriate age and elderly age groups based on their age to ascertain the therapeutic effects of CsA plus ZYP on RPL patients of different ages.Results CsA plus ZYP resulted in markedly higher E2, HCG, and P levels and live birth rates than CsA alone. After treatment with either CsA or CsA plus ZYP, the Th1 cell subset, Th1-type cytokines, and Th1/Th2 ratio significantly decreased but Th2 cell subset and Th2-type cytokines were greatly elevated in both groups, with more pronounced changes induced by CsA plus ZYP. There was no significant difference in the incidence of adverse reactions between the two groups. Furthermore, the therapeutic effect of CsA plus ZYP was better in RPL patients of appropriate age.Conclusion CsA plus ZYP significantly improved Th1/Th2 balance and increased live birth rates in RPL patients and was more effective in RPL patients of appropriate age.